A survey of the Porrhoclubiona Lohmander, 1944 from Central Asia (Araneae, Clubiondae) - Yuri M. Marusik; Mikhail M. Omelko (PENSOFT PUBL, 2022)
Clubiona Latreille, 1804, with more than 500 named species, is one of the largest genera of Araneae. The genus has 15 synonyms, most of which are not listed in the World Spider Catalog (2018) and unknown to many arachnologists. The most comprehensive survey of Clubiona sensu lato by Wunderlich (2011) also lacked a few synonyms. In this paper all genus group names described in Clubiona are listed with their type species. Most of these names correspond to the species groups recognised in Clubiona sensu lato. We agree that Porrhoclubiona Lohmander, 1944 (= Clubiona genevensis-group) deserves a status of a separate genus and provide the diagnosis of this taxon. Three species of Porrhoclubiona that occur in Central Asia are surveyed, and two of them are described as new to science: P. laudata (O. Pickard-Cambridge, 1885), comb. n. (male female, Xinjiang, Tibet, China), P. bosmansi sp. n. (male female, Tajikistan), and P. moradmandi sp. n. (male female, Fars, Iran). It seems that all records of P. genevensis L. Koch, 1866 from China refer to P. laudata. The records of Clubiona vegeta Simon, 1918 from Tajikistan and Iran refer to P. bosmansi sp. n. and P. moradmandi sp. n., respectively. The following new combinations have been established: Porrhoclubiona decora (Blackwall, 1859), comb. n., P. diniensis (Simon, 1878), comb. n., P. leucaspis (Simon, 1932), comb. n., P. minor (Wunderlich, 1987), comb. n., P. pseudominor (Wunderlich, 1987), comb. n., P. pteronetoides (Deeleman-Reinhold, 2001), comb. n., P. vegeta (Simon, 1918), comb. n., P. viridula (Ono, 1989), comb. n., and P. wunderlichi (Mikhailov 1992), comb. n. (all ex. Clubiona). SEM study of the structure considered earlier as scopula in Clubiona and Porrhoclubiona reveals that it is represented by several lateral rows of movable macrosetae (spines) with a locking mechanism.